Performance, Fermentation Characteristics and Composition of the Microbiome in the Digest of Piglets Kept on a Feed With Humic Acid-Rich Peat - Visscher, Christian; Hankel, Julia; Nies, Andrea; Keller, Birgit; Galvez, Eric; Strowig, Till; Keller, Christoph; Breves, Gerhard (Frontiers in Veterinary Science, 2019)
The transition from breast milk to solid feed is a dramatic change in the nutrition of piglets, frequently necessitating antibiotic treatment. In efforts to reduce the use of antibiotics, dietetic concepts based on natural feed additives are becoming more and more important. In the present study, experiments were carried out with 15 rearing piglets (days 28-56) divided into three groups that were offered different diets (Ctr [0% peat]; H1.5 [1.5% peat] and H3.0 [3.0% peat] based on a commercial weaner recipe; all approx. 178 g CP, 13.7 MJ, 13.3 g Lys, as-fed). The contents of cecal and colon digesta were removed at necropsy. The gas formation (4 h) in digesta was measured using in vitro batch fermenters. For microbiome studies, 16S rRNA amplification was performed within the hypervariable region V 4 and sequenced with Illumina MiSeq platform. DNA read mapping and statistical analysis were performed using QIIME (version 1.8.0), MicrobiomeAnalyst, RStudio and SAS Enterprise Guide. The mean body weight of the animals at the end of the trial did not show statistical differences (in kg: Ctr: 26.1±4.85, H1.5: 28.5±3.41, H3.0: 26.2±4.92). The daily weight gains were high for this age (in g/day; Ctr: 607±157; H1.5: 692±101; H3.0: 615±113) and the feed to gain ratio low (in kg/kg; Ctr: 1.538; H1.5: 1.462; H3.0: 1.462). Concentrations of short-chain fatty acids in the cecal content were significantly lower when peat was used (mmol/kg wet weight; Ctr: 173±30.0; H1.5:134±15.0; H3.0:133±17.3). Numerical differences were found in the gas formation (in mL gas per 10 mL batch in 4 h; Ctr: 7.9±2.2; H1.5: 7.4±2.4; H3.0: 6.6±1.1). The microbiome analyses in the cecal content showed significantly higher values for alpha diversity Chao 1 index for samples from the control group. Significant differences were found for bacterial relative abundance for Tenericutes at phylum level and Mollicutes at class level (p < 0.05) in cecal microbiota. Therefore, there was initial evidence that peat influences intestinal microflora causing a shift in the overall concentration of fermentation products in both, the cecal and the colon content.